ANALISIS STRATEGI PEMASARAN USAHA KECIL MENENGAH PADA MASA PANDEMI CORONA VIRUS (COVID-19) (STUDI KASUS UKM “TAHU BAKSO BERKAH SENTOSA SIDOARJO) - Santoso (ICO EDUSHA, 2021)
According to the minister of PPN/Bappenas, Indonesia experienced an economic growth of 0.05% due to the existence of UKM. People who have independent businesses are one of the strategies to move the wheels of the nation's economy. The Covid-19 pandemic situation provides challenges and opportunities for the Indonesian government to maintain the existence of UKM.Therefore, a short-term solution is needed for UKM and the workers who are members of them. This study aims to describe: 1. The marketing strategy applied by UKM "Tahu Bakso Berkah Sentosa" during the pandemic. 2. Marketing strategy in the development of income and assets, demand, partnerships, and labors of UKM "Tahu Bakso Berkah Sentosa.” This type of research is qualitative research. This research was conducted at the UKM Tahu Bakso Berkah Sentosa Sidoarjo from January to June 2021. The subject of this research is the owner of the UKM Tahu Bakso Berkah Sentosa . Data collection techniques using interviews, observation and documentation. The results showed that (1) The marketing strategy implemented by the UKM "Tahu Bakso Berkah Sentosa" during the pandemic was very good. (2) The marketing strategy in the development of assets and income, demand, partnership and labor has also been carried out by UKM " Tahu Bakso Berkah Sentosa ". Key Words : Maarketing, UKM, Covid -19 pandemic References Alfat, dkk. 2003. Aqidah Akhlak. Semarang: PT. Toha Putra Ibrahim dan Darsono. 2009. Membangun Akidah dan Akhlak. Solo: PT. Tiga Serangkai Pustaka Mandiri Multahim, dkk. 2007. Pendidikan Agama Islam. Jakarta: Yudistira Tim Penulis. 2009. Materi Inti dan Soal Jawab Pendidikan Agama Islam. Solo : PT. Tiga Serangkai Pustaka Mandiri Muslimin, Muhammad Irwin, and Darwanto Darwanto. "Studi Komparasi Pemikiran Ekonomi Islam Syed Nawab Haider Naqvi dengan Yusuf Al-Qardhawi." Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah 4.1 (2022): 136-161. Ghofur, Abdul. "Pengantar Ekonomi Syariah: konsep dasar, paradigma, pengembangan ekonomi syariah." (2020). Sholihin, Ahmad Ifham. Buku pintar ekonomi syariah. Gramedia Pustaka Utama, 2013. Al Arif, M. Nur Rianto, and Euis Amalia. Teori mikroekonomi: Suatu perbandingan ekonomi Islam dan ekonomi konvensional. Prenada Media, 2016. Shalahuddin, Iwan, Indra Maulana, and Teresia Eriyani. Prinsip-Prinsip Dasar Kewirausahaan. Deepublish, 2018. RIZQI AMELIA, 1742143236 (2018) ANALISIS SISTEM PENGUPAHAN UNTUK MENINGKATKAN KESEJAHTERAAN KARYAWAN DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus pada UD. Gemilang Blitar). [ Skripsi ] TASMARA, Toto. 2002. Membudayakan Etos Kerja Islami. Jakarta: Gema Insani Bertens, K. 2020. Etika Profesi. Jakarta: Gramedia Pustaka Utama Sutrisno, Edy. 2017. Manajemen Sumber Daya Manusia. Jakarta: Kencana Listyaningsih, Erna, Apip Alansori. 2020. Kontribusi UMKM Terhadap Kesejahteraan Masyarakat. Yogyakarta: Andi Indraddin, Irwan. 2016. Strategi dan Perubahan Sosial. Yogyakarta. Deepublish